2016
DOI: 10.11648/j.jgo.20160403.11
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of Obstructed Labor and Associated Risk Factors among Mothers Come for Delivery Service in Adama Hospital Medical College, Oromia Regional State, Central Ethiopia

Abstract: Abstract:Background: Obstructed labor is one of the common preventable causes of maternal and perinatal morbidity and mortality in developing countries. In the last decade among the top four causes of maternal mortality, obstructed labor /uterine rupture accounted for 36% of maternal mortality in Ethiopia. The aim of this study was to determine magnitude of obstructed labor and its associated risk factors among mothers come for delivery services in Adama Hospital Medical College from June 01 to July 30, 2015. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
3
7
1
Order By: Relevance
“…In present study, malpresentation was significantly associated with obstructed labor. This finding was almost found to be a universal fact and has been revealed in many studies [3,4,15,17] and texts [1]. This study clearly shares the limitations of cross-sectional studies and the retrospective nature of the study and lack of some important variables due to inappropriate and/or non-recording of certain variables.…”
Section: Factors Associated With the Obstructed Laborsupporting
confidence: 68%
See 3 more Smart Citations
“…In present study, malpresentation was significantly associated with obstructed labor. This finding was almost found to be a universal fact and has been revealed in many studies [3,4,15,17] and texts [1]. This study clearly shares the limitations of cross-sectional studies and the retrospective nature of the study and lack of some important variables due to inappropriate and/or non-recording of certain variables.…”
Section: Factors Associated With the Obstructed Laborsupporting
confidence: 68%
“…Gimbi Hospital (18.1%) [16]. However, this study found out a higher prevalence of obstructed labor compared to other Hospital based study in, Ilu Ababora Zone, Adama, Jimma and Mizan where 4.1%, 9.6%, 12.2% and 7.95% respectively [8,17,25,26].This variation may be due to difference in the skills of data collectors, study area and methodology. And it is lower than study West Harerghe Zone 34.3% [9] and Nigeria (20.5%) [23].…”
Section: Factors Associated With the Obstructed Laborcontrasting
confidence: 52%
See 2 more Smart Citations
“…The questionnaire was developed based on the Ethiopian Demographic Health Survey data collection tool and other relevant works of literature. 17 , 19 The questionnaire contains two parts: the sociodemographic characteristics, health facility-related characteristics, and obstetric characteristics. Data collection was carried out by five BSc midwifery as data collectors while two MSc Midwifery were nominated as supervisors for 1 month.…”
Section: Methodsmentioning
confidence: 99%